2011
DOI: 10.1097/aog.0b013e31823294da
|View full text |Cite
|
Sign up to set email alerts
|

Homicide and Suicide During the Perinatal Period

Abstract: Objective Homicide and suicide are two important and potentially preventable causes of maternal injury. We analyzed data from the National Violent Death Reporting System to estimate the rates of pregnancy-associated homicide and suicide in a multi-state sample, to compare these rates with other causes of maternal mortality, and to describe victims’ demographic characteristics. Methods We analyzed data from female victims of reproductive age from 2003–2007. We identified pregnancy-associated violent deaths as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(123 citation statements)
references
References 30 publications
5
103
1
1
Order By: Relevance
“…31 Where comparisons were available, sparse evidence suggests that pregnant/postpartum women may be at the same or lower risk for suicide compared to non-pregnant/non-postpartum women, consistent with our finding. 30, 32 Given the disproportionate burden of suicide among late postpartum women in particular, there may be important heterogeneity that is masked by calculating pregnancy-associated risk as defined (pregnant and postpartum combined).…”
Section: Commentsupporting
confidence: 87%
See 2 more Smart Citations
“…31 Where comparisons were available, sparse evidence suggests that pregnant/postpartum women may be at the same or lower risk for suicide compared to non-pregnant/non-postpartum women, consistent with our finding. 30, 32 Given the disproportionate burden of suicide among late postpartum women in particular, there may be important heterogeneity that is masked by calculating pregnancy-associated risk as defined (pregnant and postpartum combined).…”
Section: Commentsupporting
confidence: 87%
“…Other studies on pregnancy-associated homicide have reported rates per 100,000 ranging from 8.6 in Tennessee from 1989 to 1991 (postpartum only), 6 9.3 in Maryland 1993–2008, 4 2.9 in North Carolina from 2004–2006, 30 and 2.9 in 17 states participating in the National Violent Death Reporting System (NVDRS) from 2003–2007 (SC, GA, NC, VA, NJ, MD, AK, MA, OR, CO, OK, RI, WI, CA, KT, NM, UT). 31 Although we find similar rates of pregnancy-associated homicide, Samandari et al 30 concluded that the risk of homicide was decreased among pregnant/postpartum women in North Carolina based on a homicide rate of 4.9 per 100,000 in the referent non-pregnant/non-postpartum population. This estimate is notably higher than the national rate among all women reported by the Centers for Disease Control and Prevention, National Center for Injury Prevention and Control from 2005–2010 (2.9 per 100,000), 26 as well as our estimated range of 2.5–2.6 among the 37 states included in this analysis.…”
Section: Commentsupporting
confidence: 54%
See 1 more Smart Citation
“…Suicidality during the perinatal period represents a significant public health issue as it is a leading cause of maternal mortality in the USA (Chang et al 2005; Palladino et al 2011). Suicidal ideation or suicidal thoughts are significant predictors of suicide attempts and completions making suicidal ideation an important issue to address when revealed during pregnancy (Moller, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The association between IPV and depression, both during pregnancy and the postpartum period, is well-established (Agrawal et al 2014; Connelly et al 2013; Kiely et al 2013). Importantly, 54.3% of pregnancy-associated suicides involved intimate partner conflict attributable to the suicide (Palladino et al 2011). However, the association between IPV and suicidal ideation during pregnancy is under-researched.…”
Section: Introductionmentioning
confidence: 99%